Book -tax differences, analysts' forecast errors, and stock returns - Weber, David P (ProQuest Dissertations & Theses, 2005)
This thesis examines links between book-tax differences, earnings expectations and future stock returns. Book-tax differences (BTD) are discrepancies between earnings figures as calculated for financial reporting and tax purposes. My work is motivated primarily by recent academic research demonstrating BTD contain information useful for predicting future earnings and that they are associated with predictable future stock returns, leading to the conjecture that investors either ignore or misinterpret this information. However, investors' earnings expectations are not directly observable and claims of market inefficiency based on evidence of predictable future returns are always subject to the caveat of possible omitted risk factors and other research design flaws. I utilize the published earnings forecasts of professional financial analysts to overcome these issues and provide evidence on how BTD affect the expectations of both analysts and investors more generally. In the initial phase of my investigation I test the efficiency with which BTD information is reflected in analysts' forecasts of future earnings. I find that analysts' forecasts are inefficient with respect to BTD, in that their forecast errors are a function of prior BTD. Specifically, analysts' errors in predicting subsequent earnings are more optimistic for firm-years where book income is relatively high compared to tax income, consistent with failing to completely impound the information in BTD related to future earnings realizations. I then test whether systematic BTD-related errors in analysts' published earnings expectations explain the predictable future returns documented in prior research. My results indicate that analysts' errors explain investors' implied errors, as BTD no longer have incremental ability to predict future returns after controlling for analysts' forecast errors. These results support claims in prior research that investors' misperceptions of the implications of BTD for future earnings lead to mispricing and suggest that analysts' forecasts play a role in the market's anomalous behavior.